2001
DOI: 10.1359/jbmr.2001.16.10.1780
|View full text |Cite
|
Sign up to set email alerts
|

Acid Attack and Cathepsin K in Bone Resorption Around Total Hip Replacement Prosthesis

Abstract: Normal bone remodeling and pathological bone destruction have been considered to be osteoclast-driven. Osteoclasts are able to attach to bare bone surface and produce an acidic subcellular space. This leads to acid dissolution of hydroxyapatite, allowing cathepsin K to degrade the organic type I collagen-rich osteoid matrix under the acidic condition prevailing in Howship lacunae. Using a sting pH electrode, the interface membrane around a loosened total hip replacement prosthesis was found to be acidic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(125 citation statements)
references
References 35 publications
4
114
0
7
Order By: Relevance
“…Furthermore, a higher number of TRAP positive cells was seen in the synovium of the experimental group but few cells or none were seen in the control group. Histochemistry for TRAP produced results was consistent with those of an earlier study which reported an increase in the number of TRAP + cells in the synovium from humans with arthritis and dogs with osteoarthritis secondary to the naturally occurring rupture of the cranial cruciate ligament (Konttinen et al, 2001;Muir et al, 2005). These results suggest that an increase in the number of TRAP + cells in the synovium is related to the development of OA.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, a higher number of TRAP positive cells was seen in the synovium of the experimental group but few cells or none were seen in the control group. Histochemistry for TRAP produced results was consistent with those of an earlier study which reported an increase in the number of TRAP + cells in the synovium from humans with arthritis and dogs with osteoarthritis secondary to the naturally occurring rupture of the cranial cruciate ligament (Konttinen et al, 2001;Muir et al, 2005). These results suggest that an increase in the number of TRAP + cells in the synovium is related to the development of OA.…”
Section: Discussionsupporting
confidence: 89%
“…Rapidly destroyed autologous tissue (debris) in vasculitic diseases may fulfil this requirement. Finally, low pH triggers formation of polykaryons, as has been described around loosening implants [50]. Cell fusion has some important requirements: cell accumulation (density), cell adhesion and aggregation (contact) and membrane fusion (polykaryon formation by fusion).…”
Section: Dna Microarray Datamentioning
confidence: 92%
“…Thus, it seems that monocyte/macrophages, primed by indigestible particulate matter, require 'regulatory' costimulation by extracellular matrix, LPS and other exogenous soluble, cell-mediated or mechanical stimuli for fullscale activation and/or differentiation. in highly lytic lesions such as osteoclastomas [49] and aseptic loosening of hip implants [50]. Fusion can occur under the influence of either Th2 or Th1 cytokines.…”
Section: Dna Microarray Datamentioning
confidence: 99%
“…On implantation, the pH of the tissue surrounding the implant may decrease to values around 5, and then recover to 7.4 within weeks [23]. Local variations in pH value have been measured in periprosthetic tissue of revised hip implants [24,25]. Recurrence of pain in patients with cemented Mü ller straight femoral stems of Ti forged alloy was ascribed to the high acidity initiating crevice corrosion [24].…”
Section: The Human Body As a Corrosive Environmentmentioning
confidence: 99%